L’ecovillaggio di Mogliazze - Di Figlia, Luca (Scienze del Territorio, 2014)
The short paper originates from the personal visiting to Mogliazze ecovillage, a small mountain village of Apennines. The village, on the province of Piacenza (between Liguria and Emilia Romagna), presents a unique story of loss and return. Mogliazze was abandoned in 50s for migration of all inhabitants; after twenty years, from its state of decay, a project of community has flourished and has taken shape; now this project is still vital and thriving. The paper, although partially, tries to present and describe the results of this process of revitalization, based upon the principles of sharing and eco-sustainability. So, the comparison to the reality of Mogliazze and its inhabitants involves a reflective look to the settlement dynamics and the mountain territory. The fragmented story of the ecovillage, in fact, puts many considerations about the relationship between the future and ruin, between intention and action, between man and natural environment.